Audit of laboratory mycology services for the management of patients with fungal infections in the northwest of England. Issue 7 (27th June 2006) - Hassan, I A; Critten, P; Isalska, B; Denning, D W
Abstract : Background: Fungal infection is increasingly recognised as an important cause of morbidity and mortality, especially in immunocompromised patients. Little information exists on laboratory services available and the methods used by general microbiology laboratories to diagnose these important infections. Aim: To investigate the services microbiology laboratories in northwest England provide towards the diagnosis and management of superficial and deep fungal infections. Methods: A questionnaire was sent to laboratories to get a holistic view of the support given to clinicians looking after patients with fungal infections. The aim was not to investigate details of each laboratory's standard operating procedures.The completed questionnaires, which formed the basis of this report, were returned by all 21 laboratories which were recruited. This study was conducted between March 2004 and September 2004. Results: Services were provided to District General Hospitals and to six tertiary centres, including eight teaching hospitals by 16 laboratories. Their bed capacity was 250–1300 beds. Total specimens (including bacterial and viral) processed annually were 42 000–500 000 whereas fungal ones were 560–5400. Conclusion: In most microbiology laboratories of northwest England, clinicians were aware of the potential of fungal pathogens to cause infections especially in immunocompromised patients. Additional measures such as prolonged incubation of samples were introduced to improve fungal yield from patients at high risk. It is necessary to train and educate laboratory and medical staff about the role of serology and molecular methods in diagnosis and management of patients with fungal infection.